ANALISIS RASIO KEUANGAN PERUSAHAAN TAMBANG BATUBARA YANG TERDAFTAR DI BURSA EFEK INDONESIA - Luwiyanto, Luwiyanto (Katalogis, 2016)
Coal mining company's performance in the period 2008-2014 is slowing, it is caused by an economic slowdown in China dampen sales performance, coupled with jebloknya selling prices, changes in government regulations such as the ban on exports and higher royalty costs and production control could hurt earnings coal miners. This study aims to determine liquidity ratios, and profitability solvabelitas coal mining company listed on the Indonesia Stock Exchange in 2011-2014. This research is descriptive research, of the 22 population, drawn five (5) samples. namely PT Adaro Energy Tbk, PT. Bumi Resources Tbk, PT. Bayan Resources Tbk, PT. Indo Tambangraya Tbk, and PT. Tambang Batubara Bukit Asam (Persero) Tbk. Based on the research results can be summarized as follows: a) based on the results of the calculation of the liquidity ratio analysis for 4 years, there are three companies in a liquid condition, namely PT. Indo Tambangraya Tbk, PT. Coal Tambang Batubara Bukit Asam Tbk and PT. Adaro Energy Tbk, while two other companies, namely PT ilikuid conditions. Bumi Resources Tbk and PT. Bayan Resources Tbk., b)based on the results of the calculation solvabelitas ratio analysis, there are two companies in a state solvable, namely PT. Indo Tambangraya Tbk and Coal Bukit Asam Tbk, while 3 other companies, namely PT. Adaro Energy Tbk., PT. Bumi Resources Tbk, and PT. Bayan Resources Tbk. in conditions insolvabel. c) based on the results of the calculation of the main profitability ratio analysis of net profit margin then it can be concluded that PT. Adaro Energy Tbk, PT. Indo Tambangraya Tbk and PT. Bukit Asam coal mining in the condition of a profit in the year 2011-2014, while PT. Bumi Resources Tbk. and PT. Bayan Tbk.dalam a loss in 2013 and 2014.